Evaluation of an educational, theater-based intervention on attitudes toward organ donation in Risaralda, Colombia (Colombia Medica, 2013)
Introduction: The shortage of organs for transplantation is a worldwide problem and the main cause is the refusal of family members to donate. Consent to donate is influenced by many factors and educational interventions are strongly recommended.Objective: To evaluate the impact of an educational, theater-based strategy on the attitudes toward organ donation.Methodology: This study employed an intervention using theater as the central tool. The impact of this intervention on the intention to donate was assessed through a controlled, prospective, non randomized designed study. The sample consisted of 1,038 people. All the participants answered a survey that asked about sex, age and intent to donate. Afterward, one portion of the sample was exposed to the play, The Gift of Life, and a subsequent discussion forum that was guided by experts. The same survey was administered again after the intervention.Results: Before the intervention, donation attitudes were positive in 68.3% of the responses, negative in 6.8% and uncertain in 24.9%. Females showed a greater intent to donate while age had no apparent influence on the donation decision. Those exposed to the intervention were found to be more likely to donate and show a favorable change in attitude toward donation than those who were not exposed to the intervention.Conclusion: An educational intervention using theater is an effective tool to generate a short-term change in the intent to donate. Educational strategies should be employed to increase the rates of organ donation.